Design and development of nanoprobes radiolabelled with 99mTc for the diagnosis and monitoring of therapeutic interventions in oncology preclinical research - María Jimena Salgueiro; Mariano Portillo; Fiorella Tesán; Melisa Nicoud; Vanina Medina; Marcela Moretton; Diego Chiappetta; Marcela Zubillaga (SpringerOpen, 2024)
Abstract Background Previous studies employing polymeric micelles and molecular imaging for in vivo nanosystem characterization have led to the development of radionanoprobes (RNPs) designed for diagnosing and monitoring therapeutic interventions in preclinical oncology research, specifically within breast and colon cancer models. These models exhibit high GLUT1 expression on tumor cells and VEGFR expression on the tumor vasculature. We aimed to enhance the tumor-targeting specificity of these RNPs by functionalizing micelles with glucose and bevacizumab. The choice of 99mTc to label the nanoprobes is based on its availability and that direct labeling method is a widespread strategy to prepare radiopharmaceuticals using cold reagents and a 99Mo/99mTc generator. Soluplus® is an attractive polymer for synthesizing micelles that also allows their functionalization. With all the above, the objective of this work was to design, develop and characterize nanoprobes based on polymeric micelles and radiolabeled with 99mTc for the characterization of biological processes associated to the diagnosis, prognosis and monitoring of animal models of breast and colon cancer in preclinical research using molecular images. Results Four RNPs ([99mTc]Tc-Soluplus®, [99mTc]Tc-Soluplus®+TPGS, [99mTc]Tc-Soluplus®+glucose and [99mTc]Tc-Soluplus®+bevacizumab) were produced with high radiochemical purity (> 95% in all cases) and stability in murine serum for up to 3 h. The RNPs maintained the 100 nm size of the Soluplus® polymeric micelles even when they were functionalized and labeled with 99mTc. The image acquisition protocol enabled the visualization of tumor uptake in two cancer experimental models using the assigned RNPs. In vivo biological characterization showed signal-to-background ratios of 1.7 ± 0.03 for [99mTc]Tc-Soluplus®+TPGS, 1.8 ± 0.02 for [99mTc]Tc-Soluplus®, and 2.3 ± 0.02 for [99mTc]Tc-Soluplus®+glucose in the breast cancer model, and 1.8 ± 0.04 for [99mTc]Tc-Soluplus® and 3.7 ± 0.07 for [99mTc]Tc-Soluplus®+bevacizumab in the colon cancer model. Ex vivo biodistribution, showed that the uptake of the tumors, regardless of the model, is < 2% IA/g while the blood activity concentration is higher, suggesting that the enhanced permeability and retention effect (EPR) would be one of the mechanisms involved in imaging tumors in addition to the active targeting of RNPs. Conclusions Soluplus®-based polymeric micelles provide a promising nanotechnological platform for the development of RNPs. The functionalization with glucose and bevacizumab enhances tumor specificity enabling effective imaging and monitoring of cancer in animal models.